Dynamic bedrock channel width during knickpoint retreat enhances undercutting of coupled hillslopes. Issue 15 (30th September 2022) - Baynes, Edwin R.C.; Lague, Dimitri; Steer, Philippe; Davy, Philippe
Abstract: Mountain landscapes respond to transient tectonic and climate forcing through a bottom‐up response of enhanced bedrock river incision that undermines adjoining hillslopes, thus propagating the signal from the valley bottom to the valley ridges. As a result, understanding the mechanisms that set the pace and pattern of bedrock river incision is a critical first step for predicting the wider mechanisms of landscape evolution. Typically, the focus has been on the impact of channel bed lowering by the upstream migration of knickpoints on the angle, length and relief of adjoining hillslopes, with limited attention on the role of dynamic channel width. Here, we present a suite of physical model experiments that show the direct impact of knickpoint retreat on the reach‐scale channel width, across a range of flow discharges (8.3 to 50 cm 3  s −1 ) and two sediment discharges (0 and 0.00666 g cm −3 ). During knickpoint retreat, the channel width narrows to as little as 10% of the equilibrium channel width, while the bed shear stress is >100% higher immediately upstream of a knickpoint compared to equilibrium conditions. We show that only a fraction of the channel narrowing can be explained by existing hydraulic theory. Following the passage of a knickpoint, the channel width returns to equilibrium through lateral erosion and widening. For the tested knickpoint height, we demonstrate that the lateral adjustment process can be more significant for hillslope stability than the bed elevation change, highlighting the importance of considering both vertical and lateral incision in landscape evolution models. It is therefore important to understand the key processes that drive the migration of knickpoints, as the localized channel geometry response has ongoing implications for the stability of adjoining hillslopes and the supply of sediment to the channel network and export from landscapes onto neighbouring depositional plains. Abstract : The graphical abstract shows images of analogue flume experiments that highlight the width narrowing process during knickpoint retreat, and the cartoon figure shows the response of adjoining hillslopes.